2019
DOI: 10.1101/577106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of enalapril and paricalcitol treatment on diabetic nephropathy and renal expressions of TNF-α, P53, Caspase-3 and Bcl-2 in STZ-induced diabetic rats

Abstract: 21This study aimed to assess the renopreventive effect of the angiotensin converting 22 enzyme inhibitor (ACEI), enalapril, and/or vitamin D receptor (VDR) activator, paricalcitol, 23 on streptozotocin (STZ) diabetes-induced nephropathy and to elucidate the mechanisms of 24 action through investigation of the effects on renal oxidative stress, antioxidant defense 25 system and expressions of TNF-α, P53, caspase-3, and Bcl-2. Diabetes mellitus was induced 26 in fasting male Wistar rats by single intraperitoneal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…25,57 We showed that ASE treatment was able to reduce plasma levels of inflammatory cytokines and oxidative stress, suggesting anti-inflammatory and antioxidant effects promoted by ASE in this hypertension model, which may be contributing to the antihypertensive effect. The anti-inflammatory and antioxidant effects of enalapril have been previously shown, 41,58 but demonstrated to be less effective than those observed with ASE.…”
Section: Discussionmentioning
confidence: 94%
“…25,57 We showed that ASE treatment was able to reduce plasma levels of inflammatory cytokines and oxidative stress, suggesting anti-inflammatory and antioxidant effects promoted by ASE in this hypertension model, which may be contributing to the antihypertensive effect. The anti-inflammatory and antioxidant effects of enalapril have been previously shown, 41,58 but demonstrated to be less effective than those observed with ASE.…”
Section: Discussionmentioning
confidence: 94%